A Small‐Molecule Probe for Selective Profiling and Imaging of Monoamine Oxidase B Activities in Models of Parkinson's Disease. Issue 37 (21st July 2015) - Li, Lin; Zhang, Cheng‐Wu; Ge, Jingyan; Qian, Linghui; Chai, Bing‐Han; Zhu, Qing; Lee, Jun‐Seok; Lim, Kah‐Leong; Yao, Shao Q.
Abstract The design of the first dual‐purpose activity‐based probe of monoamine oxidase B (MAO‐B) is reported. This probe is highly selective towards MAO‐B, even at high MAO‐A expression levels, and could sensitively report endogenous MAO‐B activities by both in situ proteome profiling and live‐cell bioimaging. With a built‐in imaging module as part of the probe design, the probe was able to accomplish what all previously reported MAO‐B imaging probes failed to do thus far: the live‐cell imaging of MAO‐B activities without encountering diffusion problems.